Peningkatan Kesejahteraan Berbasis Maqosid Syariah Melalui Qard Hassan Yang Dimoderasi Financial Literacy di Unit Simpan Pinjam ADELWIS Demak - khajar, ibnu; Alfian, Ahmad Hijri; Nurcholis, Lutfi (Journal of Dedicators Community, 2022)
ALDEWIS is a savings and loan unit managed by RT women in Batursari,     Mranggen Demak. Established in 2007, which is currently experiencing a gap between supply and demand for funds due to the COVID-19 pandemic. A strategy is needed to make it exist and be able to serve members in particular and society in general. The objectives of community service are: (1) Providing solutions so that all productive-based loan fund needs of all ALDEWIS members can be well served, (2) Motivating the use of ALDEWIS and Qard Hassn (QH) funds for productive purposes, and (3) Motivating business results with productive motives to increase welfare based on maqosid shari'ah. The method of implementing the service is in the form of service activities based on the delivery of simple materials and training. Submission of material with an interactive, group-based and comprehensive discussion approach. The training is in the form of a simple accounting process practice. The results of community service activities: (1) The supply demand gap for credit funds was slightly helped by the QH credit package, (2) ALDEWIS members were motivated to consume ALDEWIS and QH credit funds for productive purposes after understanding the practical educational elements of QH and financial literacy as well as the accounting process simple, (3) ALDEWIS members are motivated to carry out the vision of QH donors so as to lead to the achievement of increasing the welfare of maqosid sharia.ALDEWIS merupakan unit simpan pinjam yang dikelola oleh Ibu-Ibu RT di Batursari, Mranggen Demak. Berdiri sejak tahun 2007 yang saat ini sedang mengalami gap antara suplly dan demand dana karena pandemi COVID-19. Diperlukan strategi guna membuatnya tetap eksis berdiri dan bisa melayani anggota pada khususnya dan masyarakat pada umumnya. Tujuan pengabdian masyarakat : (1) Memberikan solusi agar semua kebutuhan dana pinjaman berbasis produktif semua anggota ALDEWIS bisa terlayani dengan baik, (2) Memotivasi pemenafaatan dana ALDEWIS dan Qard Hassn (QH) untuk tujuan produktif, dan (3) Memotivasi hasil usaha motif produktif untuk peningkatkan kesejahteraan berbasis maqosid syari’ah. Metode pelaksanaan pengabdian berupa kegiatan pengabdian berbasis penyampaian materi dan   pelatihan sederhana. Penyampaian materi dengan pendekatan Diskusi interaktif, berbasis kelompok dan komprehensif. Pelatihan berupa praktek proses akuntansi sederhana. Hasil kegiatan pengabdian masyarakat: (1) Gap supply demand dana kredit sedikit terbantu dengan adanaya paket kredit QH, (2) Para anggota ALDEWIS termotivasi untuk mengkonsumsi dana kredit ALDEWIS dan QH untuk tujuan produktip setelah memahami unsur edukatip praktis QH dan financial literacy serta proses akuntansi sederhana, (3) Para anggota ALDEWIS termotivasi untuk menjalankan visi donatur QH sehingga mengarah   tercapainya peningkatan kesejahteraan maqosid syariah.